On the Shape of Limit Cycles That Bifurcate from Isochronous Center - Guang Chen; Yuhai Wu (The Scientific World Journal)
New idea and algorithm are proposed to compute asymptotic expression of limit cycles bifurcated from the isochronous center. Compared with known inverse integrating factor method, new algorithm to analytically computing shape of limit cycle proposed in this paper is simple and easy to apply. The applications of new algorithm to some examples are also given.